EFFECT OF CR, DER AND EPS ON ROS IN FOOD AND BEVERAGE CONSUMPTION COMPANIES SECTOR - Feriama Ndruru; Fransiska Esra Yana Sari Sitorus; Mindo Gita Br Silitonga; Naomi Menna R Aritonang; Holfian Daulat Tambun Saribu (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2021)
This study aims to analyze the effect of Current Ratio (CR), Debt To Equity Ratio (DER) and Earning Per Share (EPS) on Stock Returns in the food and beverage industry sub-sector companies. In determining the sample of this study using purposive sampling method, namely determining the sample by making certain criteria that are sourced from financial data on the Indonesia Stock Exchange website, there are 11 sample companies from 34 company populations. The data analysis method used descriptive statistical analysis. Hypothesis testing in this study uses the t test to determine the effect of the independent variable on the dependent variable. While the f test is used to determine the effect of Current Ratio (CR), Debt To Equity Ratio (DER), and Earning Per Share (EPS). Current Ratio (CR), Debt To Equity Ratio (DER), Earning Per Share (EPS) simultaneously have a significant effect on Stock Return. Current Ratio (CR) and Debt To Equity Ratio (DER) partially have no and insignificant effect on Stock Returns, while Earning Per Share (EPS) partially has a significant effect on Stock Returns